Mathematical model of work optimisation in the development of automated information systems - G.M. Abildinova; A.M. Aitimova (Цифровые модели и решения)
The paper presents the main components of the mathematical model represent ing the work process when creating an information system. The development of automat ed information systems requires significant expenditure of both resources and time. The process of developing an automated information system consists of numerous stages that require careful planning and management, namely analyzing system requirements, design, programming, debugging, implementation and maintenance. Estimation of the labor inten sity of programming and debugging stages is based on the approach of M. Halstead and amounts to 60-70% of the total cost of information system development. The tasks solved in this study allow us to make a step in the direction of increasing the level of information systems’ automatization. Implementation of the mathematical model of work optimization will allow increasing the overall level of development automation.